The effect of the Canada–China canola trade dispute on canola prices. (11th October 2020) - Wells, Jacob; Slade, Peter
Abstract: In March 2019, China revoked the canola export licenses of two major Canadian exporters. We estimate the impact of these restrictions on Canadian canola prices. Using a vector error correction model to generate counterfactual prices, we estimate that between March 2019 and February 2020 canola prices were 3.6% lower than would have been expected in the absence of the import restrictions. We discuss the implications of our finding for both the ongoing negotiations between Canada and China and producer support in Canada. Abstrait: En mars 2019, la Chine a révoqué les licences d'exportation de canola de deux grands exportateurs canadiens. Nous estimons l'incidence de ces restrictions sur les prix du canola au Canada. En utilisant un modèle de correction d'erreur vectorielle pour générer des prix contrefactuels, nous estimons qu'entre mars 2019 et février 2020, les prix du canola étaient 3, 6% inférieurs à ce qui aurait été attendu en l'absence des restrictions à l'importation. Nous discutons des implications de nos conclusions pour les négociations en cours entre le Canada et la Chine et le soutien aux producteurs au Canada.